1999
DOI: 10.1099/00221287-145-12-3505
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of genes responsible for the synthesis of the B-band O antigen of Pseudomonas aeruginosa serotype O6 lipopolysaccharide The GenBank accession number for the sequence reported in this paper is AF035937.

Abstract: This study reports the organization of the wbp gene cluster and characterization of a number of genes that are essential for B-band O antigen biosynthesis in the clinically prevalent Pseudomonas aeruginosa serotype O6. Twelve genes were identified that share homology with other LPS and polysaccharide biosynthetic genes. This cluster contains homologues of wzx (encoding the O antigen flippase/translocase) and wzz (which modulates O antigen chain length distribution) genes, typical of a wzy-dependent pathway. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
142
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(150 citation statements)
references
References 52 publications
(37 reference statements)
7
142
0
Order By: Relevance
“…Interestingly, the order of the same two reactions is reversed in the biosynthesis of O-antigen in P. aeruginosa O6 in which UDP-GalNAcA (5) is the substrate for the corresponding glycosyltransferases, WbpU and WbpT. 18,30 In this pathway, UDP-GlcNAc (2) is first epimerized by WbpP to give UDP-GalNAc (3), which is then oxidized by WbpO to form UDP-GalNAcA (5) (analogous to route B in Scheme 1). Apparently, a different path has been evolved in Salmonella typhi to make Vi antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the order of the same two reactions is reversed in the biosynthesis of O-antigen in P. aeruginosa O6 in which UDP-GalNAcA (5) is the substrate for the corresponding glycosyltransferases, WbpU and WbpT. 18,30 In this pathway, UDP-GlcNAc (2) is first epimerized by WbpP to give UDP-GalNAc (3), which is then oxidized by WbpO to form UDP-GalNAcA (5) (analogous to route B in Scheme 1). Apparently, a different path has been evolved in Salmonella typhi to make Vi antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the gene product of P. aeruginosa wbpP has been biochemically and genetically well characterized (1,36). Also, the enzymatic characteristics of WbpP have recently been confirmed (5).…”
mentioning
confidence: 99%
“…UDP-N-acetyl-D-galactosaminuronic acid (UDP-GalNAcA), the product of the further dehydrogenation of UDP-GalNAc, is an important intermediate used for the biosynthesis of different uronic acid sugars of surface polysaccharides that contain GalNAcA or its derivatives, not only in P. aeruginosa, but also in other organisms (36). Also, it has been recently reported that the epimerization is performed by the gene products of wbpP (1).…”
mentioning
confidence: 99%
See 2 more Smart Citations